To analyse and study art investment & its valuation - LOHIA, CHIRAYU (The journal of contemporary issues in business and government, 2021)
In today’s day and age, art is no longer limited to museums and luxurious houses for people to showcase their wealth and accomplishments. Art now has a special significance as an investment. The features of art are also considered for increasing resale value. This paper discusses the most important factors for the valuation of art and various risks and considerations before investing. Financial returns can be calculated on the basis of various factors, such as artists ’name and fame, quality of painting, growth potential, etc. There are several contemporary Indian artists like M.F. Husain, who have set a unique benchmark in the art industry and whose art has brought the trend of art investment. This paper discusses the potential of upcoming artists as well as the trend of investing in M.F. Husain’s paintings.